Pengaruh intensitas cahaya dan kadar daminosida terhadap pembungaan dan kualitas tanaman krisan dalam pot=The Effects of Light Intensities and Daminozide Concentrations on Flowering and Quality of Potted Chrysanthemum - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
The research was to study the effects of various light intensities and daminozide concentrations on early flowering and quality of potted chrysanthemum. The research was conducted at Nano village, Tawangmangu, KarangAnyar, Surakarta in the altitude of 1100 meters above sea level from November 2003 to March 2004. The planting medium was andosol soil type. The method of the experiment was based on a split plot design, consisted of two factors and five repetitions. The main plot factor was the light intensities i.e. 55%, 75% and 100%. The daminozide concentrations were used as sub plot i.e. 0 ppm, 125 ppm, 250 ppm, 375 ppm, and 500 ppm. The results of the research showed that (1). The treatment of light intensities showed no significant difference on appearence time of the first flower, but the increament of daminozide concentrations induced the plant to flower early. (2). There were interaction effects of light intensities and daminozide concentrations mainly on shoot diameter, number of flower per plant, plant volume, plant harvesting age and plant decorate age. (3). Seventy five percent of light intensity and 250 ppm daminozide concentration produced significantly the highest results as shown by shoot diameter, and number of flowers. (3). Seventy five percent of light intensity and 250 ppm daminozide concentration produced highest quality of plant.